2014
DOI: 10.1177/0363546513520295
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Bone Stress Injuries With Increasing Female Athlete Triad–Related Risk Factors

Abstract: In the sample, which included female adolescents and young adults participating in competitive or recreational exercise activities, the risk of BSIs increased from approximately 15% to 20% for significant single risk factors to 30% to 50% for significant combined female athlete triad-related risk factor variables. These data support the notion that the cumulative risk for BSIs increases as the number of Triad-related risk factors accumulates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(222 citation statements)
references
References 53 publications
5
207
2
8
Order By: Relevance
“…22 Among distance runners, concern about energy deficits is heightened because of the prevalence of eating disorders and the female athlete triad, both of which may contribute to bone loss and bone injury. 11,[23][24][25][26] We did not formally evaluate the female athlete triad, although the number of reported fractures and stress fractures is small. Nevertheless, primary prevention of disordered eating is an important strategy for risk reduction related to compromised bone density and other physiologic health consequences of inadequate energy intake.…”
Section: Overuse and Ntl Injuriesmentioning
confidence: 99%
“…22 Among distance runners, concern about energy deficits is heightened because of the prevalence of eating disorders and the female athlete triad, both of which may contribute to bone loss and bone injury. 11,[23][24][25][26] We did not formally evaluate the female athlete triad, although the number of reported fractures and stress fractures is small. Nevertheless, primary prevention of disordered eating is an important strategy for risk reduction related to compromised bone density and other physiologic health consequences of inadequate energy intake.…”
Section: Overuse and Ntl Injuriesmentioning
confidence: 99%
“…It is especially important to evaluate for the female triad: irregular menses, eating disorders, and decreased bone mineral density. Recent research revealed that the presence of female triad-related risk factors increases female patient risk of bony stress injury, especially low bone mineral density and participation of greater than 12 h of exercise per week [22]. Furthermore, there appears to be an additive effect, with more risk factors associated with greater risk of stress reaction.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In competitive track and field athletes, 21% of all athletes sustained a stress fracture in a 1-year period, with no difference between male and female athletes (56). However, young female athletes with risk factors called the "female athlete triad" (eating disorders, amenorrhea, and decreased bone density) have a cumulative higher risk for stress fractures with each of these risk factors-up to 20% for a single factor and 30%-50% for combined risk factors (57). Around the hip joint, common sites for stress fractures in athletes are the acetabulum and the femur.…”
Section: State Of the Art: Hip Imaging In Athletes Agten Et Almentioning
confidence: 99%